1991
DOI: 10.1002/clc.4960140604
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Graft atherosclerosis following cardiac transplantation: Clinical perspectives

Abstract: Summary: The advent of effective immunosuppression has made cardiac transplantation a viable treatment option for end‐stage cardiac failure, with marked improvement noted in patient survival expectation in the past decades. However, rejection episodes and infectious complications continue to be of concern in the posttransplant period. A third clinical entity, graft atherosclerosis affecting the coronary arteries, has emerged as another source of significant morbidity and mortality in patients undergoing cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Following cardiac transplantation, those patients with CMV infections are at significantly greater risk of developing accelerated post transplantation coronary atherosclerosis than are patients not infected with CMV. 6 Epidemiological data suggest that a prior CMV infection is a risk factor for restenosis of coronary arteries following coronary atherectomy. 7 Although the exact mechanism by which CMV promotes atherosclerotic coronary occlusion is unknown, some hypotheses have been made.…”
Section: Introductionmentioning
confidence: 99%
“…Following cardiac transplantation, those patients with CMV infections are at significantly greater risk of developing accelerated post transplantation coronary atherosclerosis than are patients not infected with CMV. 6 Epidemiological data suggest that a prior CMV infection is a risk factor for restenosis of coronary arteries following coronary atherectomy. 7 Although the exact mechanism by which CMV promotes atherosclerotic coronary occlusion is unknown, some hypotheses have been made.…”
Section: Introductionmentioning
confidence: 99%
“…Such atherosclerotic process usually comprises diffuse smooth muscle cell proliferation and collagen accumulation, with classical atheromatous plaques being uncommon 27 . Among consecutive heart transplant patients, Grattan showed that, compared with CMV‐negative patients, CMV‐positive individuals were at higher risk of developing early and fatal atherosclerosis 28 . These observations have been confirmed by other investigators 29 …”
Section: Infectious Agents Implicated In Atherogenesis and Chdmentioning
confidence: 68%
“…2 A member of the Herpesviridae family, CMV has been associated with an increased risk of atherosclerosis and death from coronary disease after cardiac transplant. [3][4][5] Prior CMV infection has also been linked to increased risk of restenosis after percutaneous coronary intervention. 6 However, data are conflicting with several prospective, nested, case-control studies showing disparate results.…”
Section: Infectious Agents Linked To Atherosclerosis In Recent Literamentioning
confidence: 99%